The role of the new entrepreneurial private sector in transition and economic performance in light of the successes in Poland, the Czech Republic and Hungary - Jan Winiecki (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
The central theme of this paper is the role of the new, entrepreneurial private sector, established after the fall of communism, in output recovery, and, more generally, in economic expansion of post-communist economies.This role is considered specifically in the context of the successes in Poland, the Czech Republic, and Hungary.The author notes a substantial difference between the performance of the new private sector and the privatized sector in the short to medium run (3-7 years) from the start of privatization.New private firms typically enter the economic game with well-established de jure and de facto property rights and with industrial relations based on market economy rules. Unlike the public sector or privatized firms, the labor force of these firms is not demoralized by the change to market-economy rules.As a result, they often perform better and are quick to increasing their share of aggregate output.This also helps the economy as a whole emerge earlier from transitional recession.The author discusses two hypothetical paths of recovery and expansion; one with and one without a dynamic new private sector.The determinants for establishing and growth of new private firms are considered.In addition to the specific rules and general framework of transition, the study concludes that broad institutional fundamentals of political liberty, law and order, and trust contribute to the successful emergence of this new entrepreneurial sector.
URN:NBN:fi:bof-201408072175
Keywords: 330; new private sector; transition; growth; Poland